Kajian Aspek Kosmologi Gunung Seulawah pada Arsitektur Vernakular Rumah Tinggal di Gampong Pulo - Silvi Sabila Maulida; Aghnia Zahrah; Sylvia Agustina (Jurnal RAUT, 2022)
Pulo is a village located in Mukim Lamteuba, Seulimeum sub-district, Aceh Besar district, Aceh province, Indonesia. Gampong Pulo is very close to Mount Seulawah. The residents of Gampong Pulo still use traditional Acehnese dwellings or houses, namely houses on stilts with wooden materials. Based on the explanation from the Architect Studio (2022) the material used, residential houses in Gampong Pulo are included in vernacular architecture which states that one of the characteristics of vernacular architecture is building materials that come from local locations. Vernacular architecture originates from the local environment or environmental community which forms the rules and understandings of building construction, originating from the cosmology of the universe. The purpose of this research is to identify whether there is a connection between Mount Seulawah and residential architecture in Gampong Pulo, with the research method used is a qualitative method.